Micromorphological studies on leaf, fruit and pollen of four species from Typhaceae (Typha laxmannii, T. azerbaijanensis, T. minima and T. lugdunensis) from Iran, and their thematic significance - Hamdi, Seyed Mohammad Mahdi; Assadi, Mostafa; Iranbakhsh, Alireza R. (Acta Biologica Szegediensis, 2010)
Previous research has made it clear that the intrinsic taxonomy encountered difficulties in identifying speciesin the genus Typha. Therefore, in the present study we have tried to investigate the micromorphological characteristics of pollens, achenes and leaves as well as their systematic utility. Four Typha species identified from the Iranian flora i.e. Typha minima Funk in Hoppe, Typha lugdunensis Chab., Typha azerbaijanensis Hamdi & Assadi and Typha laxmannii Lepechin were taken into consideration. Three of them are easily distinguishable with their closest relative i.e. T. laxmannii Lepechin. Scanning electron microscopy was used to examine pollens, achenes and leaves of the four taxa of the proposed Typha from Iran. A part of these micromorphological studies attempted to investigate achenes, pollens and leaf characteristics of these species under SEM. Interestingly, Typha martini Jordan is also considered as a synonym of T. lugdunensis. The study does not only discuss relationships between close species but it also clarifies their geographical patterns. Finally, a diagnostic key is provided for the distribution of the four Typha species in Iran. The results show that the ornamentation characters of pollens, achenes and leaf cells prove to be very helpful. Ornamentation of pollens and achenes could be used to distinguish between the four morphological types. Micromorphological studies on achenes, pollens and leaves of Typha were found useful with respect to taxa differentiation, hence it provides a key to make distinctions between species orgroups of species.